The role of transnational agrarian corporations in shaping Ukraine’s food security during the war - Lytvyn, Inna (My University, 2024)
The paper examines the role of transnational agrarian corporations in strengthening Ukraine’s food security during the war. Disruptions in logistics, destruction of infrastructure, and shortages of essential resources have increased the importance of corporations such as Cargill, Bunge, ADM, Bayer, Syngenta, and others. Their investment, technological support, and participation in alternative export routes have helped stabilize production, maintain export flows, and support farmers. At the same time, the study highlights risks related to market concentration and the displacement of smaller producers. The paper concludes that effective cooperation between the state and transnational corporations is crucial for restoring Ukraine’s agricultural resilience. У статті досліджується роль транснаціональних аграрних корпорацій у зміцненні продовольчої безпеки України під час війни. Перебої в логістиці, руйнування інфраструктури та дефіцит основних ресурсів підвищили значення таких корпорацій, як Cargill, Bunge, ADM, Bayer, Syngenta та інших. Їхні інвестиції, технологічна підтримка та участь в альтернативних експортних маршрутах допомогли стабілізувати виробництво, підтримувати експортні потоки та підтримувати фермерів. Водночас у дослідженні висвітлюються ризики, пов'язані з концентрацією ринку та витісненням дрібних виробників. У статті робиться висновок, що ефективна співпраця між державою та транснаціональними корпораціями має вирішальне значення для відновлення стійкості сільського господарства України.
Keywords: кафедра міжнародної економіки; food security; war; agricultural exports; investment; logistics; agribusiness; agribusiness; транснаціональні аграрні корпорації; війна; експорт сільськогосподарської продукції; інвестиції; логістика; агробізнес; агробізнес